THE E3I VILLAGE CONCEPT - abdullah, kamaruddin (185P -3466)
The E3i concept stands for empowerment the rural society in getting a better access to renewable energy sources for economic and productive activities in an environmentally sound sustainable development. This concept, proposed by the author, is meant to create the spirit of self help among the rural society who have been living in prolonged poverty and lack of access to basic energy need, especially in recent years when the price of oil becomes uncertain. Indonesia, now, is a net oil import country. Therefore, the need to tap locally available renewable energy sources is becoming an important issue. Initial works to establish the E3i village was first conducted in 1999 using the grassroots project from Japan in which several small processing units were installed in some villages in Java, Bali and West Nusa Tenggara. SPU as the value-added facilities could provide more jobs as source of income for the villagers. The paper provides more information on continuing activities in an effort to realize the E3i village concept. The importance of making use locally available renewable energy sources as the main energy input for the SPU has now gradually being appreciated by both the central and local government including the private sector.